An investigation of the relationship between intensity of grief and coping patterns of parents of individuals affected by psychotic disorders - Perera, Kanthi (Curtin University, 2003)
This study investigated the relationship between intensity of grief and coping patterns of parents of individuals affected by psychotic disorders. The study investigated the intensity of grief in a sample of parents of individuals with psychotic disorders in Western Australia to determine if the results replicate international studies. It further examined if the characteristics of the psychotic disorders of children, had an impact on the grief reactions of parents and if the disorder had a measurable impact on the nature of the relationship between parents and children. The study also identified specific coping strategies that parents consider as being most helpful to them in dealing with their grief, the relationship between intensity of grief and coping patterns of respondents and gender differences in grieving and coping strategies. The research findings suggest that there is measurable grief in a cross section of parents of individuals with psychotic disorders in Western Australia with many similarities to studies done internationally. The findings also suggest that this grief increases in intensity from the time of first diagnosis and peaks at 1-2 years after diagnosis and again 20 years after diagnosis. There was a strong association between past behaviours related to grief reactions and present feelings related to grief. To the best of my knowledge, these findings have not been reported before. IV Certain characteristics of the disorder of children had an impact on the grief reactions of the parents. Higher levels of grief were reported in parents whose children needed frequent assistance with personal care and children with a late onset of the disorder.There was a positive correlation in parents who had a close relationship with the child before the onset of the disorder and following onset of the disorder suggesting that the disorder did not affect the relationship. To the best of my knowledge, these findings have not been reported before. While this research has replicated other studies, it has also researched coping strategies that have not been identified before. Although cognitive coping strategies were most frequently used by parents and subjectively found to be more helpful, parents using predominantly behavioural methods of coping showed less intensity in their grief. Parents oscillated between approaching the feelings of grief and distracting themselves from them, which highlighted the idiosyncratic nature of coping. Although there were no gender differences in the intensity of grief, there were distinct differences in coping strategies used by fathers and mothers. These findings have important implications for social work practice and policy development within the mental health settings of Western Australia.